2020
DOI: 10.1101/2020.10.20.344556
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

From miRNA target gene network to miRNA function: miR-375 might regulate apoptosis and actin dynamics in the heart muscle via Rho-GTPases-dependent pathways

Abstract: MicroRNAs (miRNAs) are short single-stranded non-coding RNA molecules, which are involved in regulation of main biological processes, such as apoptosis, cell proliferation and differentiation, through sequence-specific interaction with target mRNAs. In this study we propose a workflow for predicting miRNAs function by analyzing the structure of the network of their target genes. This workflow was applied to study the functional role of miR-375 in the heart muscle (myocardium), since this miRNA was previously s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…The association of downregulated circulating miR-375 levels with myocardial infarction (MI) has been studied before [ 45 ]. A further study identified PIK3CA, MAPK3, PAFAH1B1, RHOA, ERBB2, MYC, PRKCA, CTNNB1 and CDC42 as crucial genes in the miR-375 regulated network and predicted the possible function of miR-375 in the heart muscle, consisting mainly in the regulation of the Rho-GTPases-dependent signaling pathways, therefore, miR-375 may function as a regulator for apoptosis in the heart muscle relaying on Rho-GTPases-dependent pathways [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The association of downregulated circulating miR-375 levels with myocardial infarction (MI) has been studied before [ 45 ]. A further study identified PIK3CA, MAPK3, PAFAH1B1, RHOA, ERBB2, MYC, PRKCA, CTNNB1 and CDC42 as crucial genes in the miR-375 regulated network and predicted the possible function of miR-375 in the heart muscle, consisting mainly in the regulation of the Rho-GTPases-dependent signaling pathways, therefore, miR-375 may function as a regulator for apoptosis in the heart muscle relaying on Rho-GTPases-dependent pathways [ 46 ].…”
Section: Discussionmentioning
confidence: 99%